Industrial training report: TNG Digital Sdn. Bhd. - Mohd Radzi, Anwar Ibrahim (Faculty of Business and Management, 2025)
This report covers my six-month internship experience at TNG Digital Sdn. Bhd. in the Funding Management Department. It provides an overview of the company, my key roles and responsibilities, the challenges I encountered, and the skills I developed throughout the internship. I was responsible for handling Reload PIN and Direct Credit operations, including tasks like processing orders, managing PIN validation and regeneration, extending validity periods, and analyzing sales data to identify trends. I also worked closely with the team on marketing communications, such as email campaigns, social media, and in-app communication (eWallet), ensuring that all campaigns aligned with the company’s objectives. The report includes a SWOT analysis of the Reload Business, highlighting its strengths, weaknesses, opportunities, and threats, along with recommendations for improvements. This internship was not without its challenges. I had to manage multiple client requests while maintaining seamless communication across departments. However, these experiences taught me valuable lessons in time management, teamwork, and problem-solving. The skills I gained, such as data analysis, campaign coordination, and effective communication with senior management, will undoubtedly support my career growth. Reflecting on this internship, I am proud of how much I have grown both personally and professionally. It has strengthened my determination to build a career in business and marketing and has given me the confidence to tackle new challenges ahead.